ANALISIS KEBIJAKAN PENDIDIKAN - Erik Purwanti; Farid Setiawan; Amalia Ririh Pertiwi; Purwaningsih Purwaningsih (Sekolah Tinggi Pariwisata Mataram, 2021)
Education is very important to educate human life. A nation will progress if its education is very much considered and even prioritized. This article aims to describe the educational policy analysis model.This research uses literature study which explains the definition of education policy analysis, the function of education policy analysis and the urgency of education policy analysis. Education that runs in an institution cannot be separated from government interference, this is of course because of its policies that are used as guidelines in achieving the goals or vision and mission of an educational institution.The implementation of an educational policy at an educational institution will certainly be one of the determinants of the success of the objectives of education.